Jakość wód zrzutowych oczyszczalni ścieków w Świebodzinie i metody zmniejszenia zawartości fosforu = The quality of the waste dump of the waste-water treatment plant in Świebodzin and the methods of reducing contents phosphorus - Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of the quality analisis of the sewage flowing to the waste-water treatment plant as well as the water after the waste-water treatment plant in Świebodzin have been presented in the article. It has been found that the waste-water after cleaning does not meet the requirements concerning phosphorus, that is why in the next part the method of eliminating phosphorus by means of fractional precipitation of iron salts and establishing the optimum dose of coagulants has been dealt with.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)